Effects of smart meter privacy protection management on the lifetime performance of 18, 650 lithium‐ion batteries. Issue 2 (29th October 2021) - Pham, Cong‐Toan; Månsson, Daniel
Abstract: Concerns over privacy leaks through real‐time monitoring in smart meters (SMs) raise questions about how to effectively protect the user power consumption data. As one potential solution, energy storage systems have been suggested to physically manipulate SM readings to hide the true load pattern. Lithium‐ion batteries (LiBs) are commonly utilised in the residential area in various applications such as solar and home batteries. Its use in a privacy‐focussed operation has shown potential with reasonable system sizes in the range of commercially available products. However, batteries are subjected to ageing and the deterioration of performance over the course of time, which can limit the feasibility in such application. Hence, this work aims to investigate the ageing influence on LIBs' performance to deduce the life expectancy and how well privacy is protected over time. The study includes ageing tests with a specifically designed cycle life test procedure for the privacy protection scheme to extract relevant model parameters for the equivalent circuit battery model.